Micro Social Movements: Informal Empowerment Practices in Villages as a Response to Social Inequality - Zainudin, Zainudin; Ediyono, Suryo (Socious Journal, 2025)
Micro social movements in rural areas represent collective community responses to persistent social inequality, particularly when formal interventions fail to address local needs. This study explores how informal empowerment practices function as micro social movements that are adaptive, community-based, and grounded in local agency. A Systematic Literature Review was conducted following identification, screening, eligibility assessment, and synthesis using Snyder’s guidelines. A total of 22 selected articles were analyzed through content analysis to examine patterns, strategies, and impacts of informal empowerment in addressing inequality. The findings indicate that micro social movements emerge through the interaction of social capital, informal structures, micro social innovations, and community participation. Social capital serves as the primary foundation enabling collective action, while informal structures such as self-help groups and traditional institutions act as social learning spaces. Social innovations, including digital technology adoption and local economic initiatives, enhance community capacity to respond to inequality. The study concludes that informal empowerment plays a strategic role in strengthening rural social resilience and fostering community autonomy. Structural implications include strengthening village policy frameworks, integrating digital technology, enhancing local leadership capacity, and promoting multi-actor collaboration to sustain micro social movements